TERM PLACENTAL ABRUPTION RATES IN HYPERTENSIVE PREGNANCIES: A PROSPECTIVE EPIDEMIOLOGICAL STUDY (The Research of Medical Science Review, 2025)
Background The early separation of the placenta from the uterine wall, or placental abruption results in a very serious complication that is associated with many risks for both mother and baby. The main factors responsible are hypertensive disorders, chronic hypertension and preeclampsia due to altered blood flow at the placenta level which has also injury oxidative because of vascular ischemia. Placental abruption was almost 4 times more likely in hypertensive than normotensive pregnancies. If it occurs at term (after 37 weeks),then induction is required and the mother can hemorrhage or fetal distress result. Either way, abruption has long been a central concern in the care of women with hypertensive pregnancies. Methodology This was a descriptive cross-sectional study, conducted among 154 hypertensive pregnant women at Shaikh Zayed Women Hospital SMBBMU Larkana. The non-probability consecutive sampling technique was used to recruit the women. Continuously monitor and record the blood pressure to ensure accurate and consistent measurements. Schedule ultrasound examinations for all identified cases of hypertension were done to assess the placental abruption based on including retroplacental hematoma, intraplacental anechoic areas, placental thickening over 5.5 cm, and intra-amniotic echoes. Data were analyzed using SPSS ver. 26 for Windows (IBM Corp.). Data will be entered and analyzed by SPSS version 26. Descriptive statistics will be calculated, and data will be analyzed and generated with 95% confidence interval. Results The mean ± SD of age of the participants was 30.56 ± 10.13 years, with a majority (55.8%) in the age range of 18-30 years, while 44.2% were older than 30 years. The mean diastolic blood pressure (DBP) was 90.91 ± 4.69 mmHg, with 54.5% having DBP between 80-90 mmHg and 45.5% over 90 mmHg. The placental abruption was found to be in 29 (18.8%) women. Systolic and diastolic blood pressures were slightly higher in the abruption group (137.24 ± 10.31 mmHg SBP and 91.55 ± 4.45 mmHg DBP) compared to those without abruption (136.68 ± 9.48 mmHg SBP and 90.76 ± 4.75 mmHg DBP) with (p=0.778 for SBP and p=0.415 for DBP). Conclusion This study found insignificant associations between term placental abruption rates in hypertensive pregnancies and factors like age, BMI, gestational age, or blood pressure. Although abruption was slightly more common in patients with elevated systolic and diastolic pressures, these differences were statistically insignificant, underscoring the need for further research to validate these findings.